Paradigm Shift in Islamic Studies (Al-Jamiah Research Centre, 2008)
In the early 1990s, there was a heated debate among students of IAIN (the State Institute for Islamic Studies) Sunan KalijagaYogyakarta about the future of Islamic studies, focusing on the possibilityof incorporating Thomas Kuhnâs paradigm to the discourse ofIslamic studies. Kuhn explains in detail the rise and decline of scientificparadigm in his classic work, The Structure of Scientific Revolutions,firstly published in 1970. Paradigm is defined as a set of beliefs thatguides the researchers to address some important problems or issuesunder a certain theoretical framework and provides procedures how tosolve those problems. A paradigm shift is a process whereby a newway of perceiving the world comes into existence and is accepted byscholars in a given time. Kuhn proposed two conditions for paradigmshift; first, the presence of anomalies in ânormal scienceâ, and secondly,the presence of alternative paradigm.